2020
DOI: 10.1038/s41598-020-75108-3
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus secretes immunomodulatory RNA and DNA via membrane vesicles

Abstract: Bacterial-derived RNA and DNA can function as ligands for intracellular receptor activation and induce downstream signaling to modulate the host response to bacterial infection. The mechanisms underlying the secretion of immunomodulatory RNA and DNA by pathogens such as Staphylococcus aureus and their delivery to intracellular host cell receptors are not well understood. Recently, extracellular membrane vesicle (MV) production has been proposed as a general secretion mechanism that could facilitate the deliver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 73 publications
(125 reference statements)
4
70
0
Order By: Relevance
“…In short, MVs serve as messengers between the host and the pathogen and are also used for defense. It is very important that pathogen-derived MVs carrying pathogen particles could elicit a host immune response by activating immune cells including monocytes, macrophages, T cells and NK cells [ 184 , 185 , 186 ]. Thus, MVs could be considered as a potential vaccine candidate against infectious diseases.…”
Section: Role Of Mvs In Infectious Diseasesmentioning
confidence: 99%
“…In short, MVs serve as messengers between the host and the pathogen and are also used for defense. It is very important that pathogen-derived MVs carrying pathogen particles could elicit a host immune response by activating immune cells including monocytes, macrophages, T cells and NK cells [ 184 , 185 , 186 ]. Thus, MVs could be considered as a potential vaccine candidate against infectious diseases.…”
Section: Role Of Mvs In Infectious Diseasesmentioning
confidence: 99%
“…Regarding nucleic acids, in the study by Andreoni et al, quantification with PicoGreen dsDNA kit revealed the association of DNA molecules to S. aureus EVs [68]. Finally, Rodriguez and Kuehn recently demonstrated that S. aureus Newman strain secrets EVs containing DNAs of ~500 base-pair long and RNAs with sizes of <300 nucleotides in length [70]. However, further investigations are necessary to better characterize the nucleic acid content of S. aureus EVs.…”
Section: S Aureus Vesicle Cargo: Other Componentsmentioning
confidence: 99%
“…A recent study conducted by Rodriguez et al demonstrated that nucleic acid associated with S. aureus EVs is immunomodulatory [70]. They identified DNA and RNA populations associated with EVs derived from Newman strain and provided evidence that these nucleic acids are delivered into host endosomal compartments [70]. In vitro experiments showed that murine macrophages exposed to EVs presented a strong IFN-β mRNA expression after 3 hours of stimulation [70].…”
Section: S Aureus-evs In Immunomodulationmentioning
confidence: 99%
See 2 more Smart Citations